Comparative analysis of risk factors of typhoid fever occurrence in different villages of Astore valley, Gilgit Baltistan Pakistan - Komal, Salma; Younus, Waqar; Hussain, Azhar; Ali, Sartaj; Hussain, Syed Arif; Hussain, Ikhlaq (International Journal of Pathology, 2025)
Background:  Salmonella enterica serotype Typhi and, to a lesser extent, serotypes Paratyphi A, B, and C, cause typhoid fever. Higher prevalence of typhoid is a concern, particularly with remote areas in Astore valley. This study was conducted to investigate the risk factors, vulnerable segments of population, and the efficacy of antibiotics against typhoid pathogen.Methods: Study was conducted in District Astore from October 2022-august 2023, which encompasses a population exceeding 70,000 individuals residing across more than a hundred communities. Choungrah, Eidgah, Gorikot, Louse, and Harcho were selected as research sites from five distinct villages. This study utilized modern statistical tools to investigate the risk factors associated with typhoid incidence in multiple villages. The research involved both diagnostic and community-based surveys. Microbiological analysis of water samples was conducted using the pour plate technique, while antibiotic susceptibility tests on bacterial colonies were initially performed using disc diffusion methods.Results:  In Choungrah tap water, the bacterial load was 180.10 cfu/ml, while Gorikot tap water had the lowest load 61.33 cfu/ml. Gorikot pipe water had the highest Salmonella species concentration at 11.33 × 10^5 cfu/ml, with Eidgah tap water at 2.33 × 10^5 cfu/ml being the lowest. Ciprofloxacin was most effective antibiotic, while cefixime showed the least efficacy, indicating increased bacterial resistance. Regarding water sources, 70.66% preferred tap water, 16.68% spring water, and 12.66% bottled water. Drainage systems and waste collection techniques were reported insufficient by the majority. Three-quarters consumed street food, with only 5% practicing hand washing before and after meals. 30.33% of males (56.66%) and 18% of females (43.33%) had experienced typhoid fever, while 62% of respondents were aware of illness.Conclusion: The study reveals a significant prevalence of typhoid fever in the Astore valley, underscoring multiple risk factors including contaminated water sources, poor hygiene practices, and inadequate sanitation.